Painful Os Peroneum Syndrome Secondary to Hydroxyapatite Deposition Disease - Shashank Chapala; Vijay Ram Kumar Papineni; Asad Rabbani Shah; Moez Ballal; Karthikeyan P. Iyengar; Rajesh Botchu (Indian Journal of Radiology and Imaging)
Painful os peroneum syndrome (POPS) is one of the uncommon causes of lateral foot pain in orthopaedic practice. POPS encompasses a spectrum of pathologies such as an acute or a chronic fracture, peroneus longus tenosynovitis, and attrition or partial rupture of the peroneus longus tendon. Herein, we reported the first case of POPS secondary to hydroxyapatite deposition disease in a 32-year-old female patient. The clinical presentation, the role of radiological interventions, particularly ultrasound-guided barbotage in its diagnosis and effective management, is highlighted.